2012
DOI: 10.1016/j.rmed.2011.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of whole body vibration in patients with chronic obstructive pulmonary disease – A randomized controlled trial

Abstract: WBV training seems to be a promising new exercise modality for patients with COPD and may enhance the effects of a multidisciplinary rehabilitation program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
110
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(118 citation statements)
references
References 41 publications
1
110
1
4
Order By: Relevance
“…The 3-week exercise training program employed in this study was a component of a comprehensive, multidisciplinary, inpatient PR program [13]. The exercise training program consisted of daily endurance training on a cycle ergometer [60% of peak work rate (PWR)] and resistance training for large muscle groups (3 sets with 20 repetitions).…”
Section: Methodsmentioning
confidence: 99%
“…The 3-week exercise training program employed in this study was a component of a comprehensive, multidisciplinary, inpatient PR program [13]. The exercise training program consisted of daily endurance training on a cycle ergometer [60% of peak work rate (PWR)] and resistance training for large muscle groups (3 sets with 20 repetitions).…”
Section: Methodsmentioning
confidence: 99%
“…New training modalities besides conventional exercise methods, such as neuromuscular electrical muscle stimulation [49,50], inspiratory muscle training [51,52], whole-body vibration training [53], or noninvasive ventilation [54,55], have been shown to be beneficial in patients with advanced COPD. It could be hypothesized that these therapeutic interventions may also be useful in IPF.…”
Section: Unmet Needs For An Ipf-specific Pr Approachmentioning
confidence: 99%
“…Pulmonary rehabilitation improves exercise performance, dyspnea, and quality of life, reduces the effects of acute exacerbations and prolongs the interval between exacerbations [5,6]. Current guidelines recommend pulmonary rehabilitation for all stages of COPD but do not explicitly recommend it during an acute exacerbation [1].…”
Section: Introductionmentioning
confidence: 99%
“…Whole body vibration (WBV) is a novel exercise training modality performed on a vibrating platform that moves in sinusoidal oscillations, during which static and dynamic exercises can be performed [6]. A randomized clinical trial has demonstrated greater improvements in a number of exercise tests in the group of COPD patients (GOLD stages III and IV) trained on the WBV platform compared to a group that was conventionally trained [6].…”
Section: Introductionmentioning
confidence: 99%